IMPLEMENTASI NILAI KARAKTER MELALUI PROGRAM BIMBINGAN KONSELING DI SD NEGERI 16 TOBOALI BANGKA SELATAN - Okta Praditya, Ginza; Arief, Ardian; Rahim, Abdul; Taryatman, Taryatman; Ardhian, Trio; Hanifudin Najib, Khotim (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to describe 1) the planning of the Counseling Guidance program in character value formation learning activities 2) the implementation of Counseling Guidance in character value formation learning activities, 3) the obstacles in the implementation of Counseling Guidance to build character values. This research was conducted at SD Negeri 16 Toboali, South Bangka. This research was conducted in October 2021. The data sources in this study were principals, teachers, and students. Data collection techniques using observation techniques, interviews, and documentation. The data analysis technique in this study uses Miles and Huberman analysis which consists of data collection, data reduction, data presentation, and concluding. The results of the study, 1) Planning for counseling guidance is very important to be carried out to build character values ​​in learning activities carried out by teachers by adjusting students' needs so that the purpose of planting character values ​​can be carried out properly. 2) Class teachers as supervising teachers have implemented character values ​​through counseling programs both classically and individually in learning activities. 3) Obstacles faced by teachers in implementing character values ​​through counseling are some students who still commit violations even though they have been given guidance, lack of openness of students to teachers, and lack of time for teachers to implement them. In addition, the teacher also cooperates with related parties and utilizes the time as much as possible to minimize violations committed by students.